Pengaruh Green Human Resource Management, Green Human Capital dan Green Innovation Terhadap Environmental Performance Melalui Green Human Capital dan Green Innovation pada PT Mitrakarya Cipta Gemilang - Elysabeth Jane Pramudita; Andreas Wahyu Gunawan (Glosains: Jurnal Sains Global Indonesia, 2023)
This study describes that the application of GHRM practices can be seen from the attractiveness of employee selection, including having a commitment to environment. Followed an evaluation carried out more emphasis on environmental performance. In addition, company managers also fully support employees for environmental sustainability policies and support for environmental competence. The test results also prove that the company really considers eco-labeled products, including reducing the use of raw materials in the manufacturing process. Another thing in the test proves that there is an organization's partnership with environmentally friendly suppliers. The results of this study provide insight and help develop knowledge on environmental sustainability for the managerial level that influences the impact of Green Human Resource Management, Green Human Capital and Green Innovation on Environmental Performance Through Green Human Capital and Green Innovation. The four variables were developed into 21 (twenty one) measurement indicators. There are 8 (eight) hypotheses tested to analyze Environmental Performance in PT. Mitrakarya Cipta Gemilang. The research findings show that from the development of 8 (eight) hypotheses, there are 5 (five) hypotheses that are supported by a significant and positive effect; and there are 3 (three) hypotheses that are not supported. From the resulting model it has been proven that GHRM has an effect on Environmental Performance mediated by Green Human Capital.